2016
DOI: 10.1016/j.drugalcdep.2015.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the CAGE questionnaire for men who have sex with men (MSM) in China

Abstract: Background Detection of heavy drinking among men who have sex with men (MSM) is crucial for both intervention and treatment. The CAGE questionnaire is a popular screening instrument for alcohol use problems. However, the validity of CAGE for Chinese MSM is unknown. Method Data were from three waves of cross-sectional assessments among general MSM (n=523) and men who sell sex to other men (“money boys” or MBs, n=486) in Shanghai, China. Specifically, participants were recruited using respondent-driven, commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The CAGE (focusing on Cutting down, Annoyance by criticism, Guilty feeling, and Eye-openers) four-item questionnaire was used to measure HD (see Supplementary Materials Table S1 ). The four items were summed using scoring from 0 to 4 [ 25 ]. A higher score indicates an alcohol-related problem and a total of 2 or more is considered to signify the prevalence of HD, which is clinically significant [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CAGE (focusing on Cutting down, Annoyance by criticism, Guilty feeling, and Eye-openers) four-item questionnaire was used to measure HD (see Supplementary Materials Table S1 ). The four items were summed using scoring from 0 to 4 [ 25 ]. A higher score indicates an alcohol-related problem and a total of 2 or more is considered to signify the prevalence of HD, which is clinically significant [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study found that workplace social capital was a protective factor for HD [ 25 ], but it mainly focused on an occupational population. Considering the previous findings about the mixed effects of the structural and cognitive components of social capital on HD, our study’s aim was to examine the relationship between some indicators of social capital at individual- and district-level, including social cohesion and membership in social organizations with the frequency and prevalence of HD.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs use in any context (recreational use) : alcohol consumption (last 12 months), alcohol abuse (assessed using CAGE4 questionnaire, which is a screening tool widely used to measure alcohol abuse and dependence in a population [ 36 ]), drugs consumed in any context (last 12 months), and injection drug use (sometime in life).…”
Section: Methodsmentioning
confidence: 99%
“…Depression, anxiety, and post-traumatic stress were screened by Patient Health Questionnaire 9-item scale (PHQ-9) score ≥ 10, [29] Generalized Anxiety Disorder 7-item scale (GAD-7) ≥ 10, [30] and PTSD Checklist for DSM-5 (PCL-5) ≥ seven. [31] Substance Use Disorder (SUD) was determined by a CAGE-AID Questionnaire [32] score of ≥ 1.…”
Section: Assessmentsmentioning
confidence: 99%